Estudo da antinocicepção induzida pelo ultrasom terapêutico no modelo experimental de dor neuropática trigeminal, em ratos - Atila Savernini Lopes (2006)
The trigeminal neuralgia (TN) is considered one of the most painfulconditions, where the pharmacological treatment can be as debilitating as the pathology itself. The aim of this work was to evaluate the effectiveness of pulsed Therapeutic Ultrasound (USt) on an experimental model of trigeminal neuropathic pain (Infraorbital Nerve - Chronic Constriction Injury; CCI-ION), in rats. An apparatus for evaluation of facial thermonociception was developed and named of termoalgesímetro: a constant heat source is applied on the vibrissal pad of rats andtime spent for head withdraw-reaction is evaluated in seconds. This method was able to detect the increase (hypoalgesia) or decrease (hyperalgesia) of basal values. After the surgery of CCI-ION, a gradual reduction in head-withdrawal latencies was observed within the postoperative period. The values became constants from the14th-16th day post-CCI (pre-CCI= 11.29 ± 0.27s; post-CCI= 4.60 ± 0.13s; p<0.001). No changes on withdrawal-latencies were observed on sham-operated or naïve animals. Three ipsilateral applications of USt (ERA 1 cm2, pulse 1:5, frequency 100 Hz, intensity 0.4 W/cm2 e 0.3 W/cm2) on post-CCI rats were able to increase the head-withdrawal latencies. This antinociceptive effect was evident since the first evaluation, made 2h after de 1st USt application (6.79 ± 0.15s; p<0.05). The antinociception reached maximum values at 24th h, when the latency was greater than preoperative basal values (14.29 ± 0.67s; p<0.001), evidencing a hypoalgesic effect. The magnitude of the antinociceptive effect was directly proportional to the intensity of the ultrasonic wave. There was no effect when the massage was done with not powered (off) US-apparatus (USt-). Pre-treatment with Naltrexone (5mg/kg; s.c.) was unable to block the antinociceptive effect of the USt during the first 8 h (9.41±0.64, p<0.05), although post-treatment with the opioid antagonist, given at the 23th ½ h, completely blocked the hypoalgesic effect, bringing the values back to the USt- levels (UST-= 4.48 ± 0.25; USt+NLF23th= 5.05 ± 0.56s). These results indicate that an opioidergic mechanism is involved only on the latter phase of USt effects. The levels of MPO in the infraorbital nerve were increased on the 3rd day post-surgery and were back to basal values by the 15th day (3rdday= 729,30 ± 88,25; 15thday= 320,67 ± 157.0 %, taking mean pre-surgery values as 100%), suggesting that neutrophils are present only in acute pos-surgical phase. The USt did not modify the MPO levels. We concludes that the USt is a potentially useful and efficient resource in the treatment of trigeminal neuralgia. Nevertheless, more research is necessary to elucidate the mechanisms involved in antinociception induced by USt.